IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH QUESTIONING TECHNIQUE - Eva Saskia Rahma and Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study concerned with the improvement of students’ achievement in writing descriptive text by applying Questioning technique. The objective of this study was to discover whether questioning technique could significantly improve students’ achievement in writing descriptive text. It was conducted by using classroom action research which was carried out in two cycles in six meetings. The subject of the research was class VIII-1 SMP Negeri 2 Lima Puluh. The number of the students was 30. The instruments for collecting data were writing tests as the quantitative data and diary notes, observation sheet, questionnaire sheet as qualitative data. Based on the students’ writing test, the students’ score was improved in every test. In the first test, the mean score was 59.86. In the second test, the mean score was 67.80. In the last test, the mean score of the students was 74.63. In the line with the data, it was showed that questioning technique significantly improved students’ achievement in writing descriptive text.